(untitled) (Research, Society and Development, 2021)
Most pregnancies are uneventful, however some women have an unfavorable evolution classified as high-risk pregnancy. Among the diseases that can develop during pregnancy, the Specific Hypertensive Syndrome in Pregnancy (SHEG) stands out, considered one of the main causes of fetal maternal mortality. The aim of this study is to know the profile of pregnant women attended at Basic Health Units (UBS) in the city of Cáceres-MT in 2020, in order to identify the risk factors that influence the onset of the disease and its complications. This is a qualitative and quantitative descriptive field study, carried out with 16 pregnant women between the months of June and July 2020. For data collection, a questionnaire with closed and open questions was designed and applied. There was a higher prevalence of women aged 32 to 37 years (50%), brown (68.75%), married (37.5%), with complete high school (37.5%) with family income and mostly without jobs (56, 25%). They had a family history of hypertension (87.5%) and diabetes (50%), were multiparous (43.75%) and were obese (75%). Prenatal monitoring remains one of the important measures in the prevention and health care of the bionym (mother-fetus) contributing to the reduction of cases of fetal maternal mortality, since SHEG is still considered an important complication during the period pregnancy and childbirth, with high risk of maternal and perinatal mortality, representing high rates of incidence and prevalence.